2013
DOI: 10.1016/j.cplett.2013.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Pt and TCO free hybrid bilayer silver nanowire–graphene counter electrode for dye-sensitized solar cells

Abstract: Here we report a novel transparent conductive oxide (TCO) and Pt free silver nanowire and graphene nanoplatelet (AgNW-GNP) based hybrid counter electrode (CE) for dyesensitized solar cells (DSSCs) having appreciable photovoltaic performances compared to reference Pt-FTO based DSSCs. Simple solution processed bilayer AgNW-GNP hybrid CEs were prepared to investigate its applicability in DSSCs based on their electrocatalytic and charge transport properties. DSSCs prepared with AgNW-GNP hybrid CEs containing the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The optically transparent GNP electrode turned out to be highly active for [Co(bpy-pz) 2 ] 3+/2 mediator [36] and even more for [Co(bpy) 3 ] 3+/2+ [35]. Al-Mamun et al [128] demonstrated a possibility of fabrication of FTO-free electrode based on graphene nanoplatelets. They combined GNP with silver nanowires, which themselves have poor electrocatalytic activity for [Co(bpy) 3 ] 3+/2+ .…”
Section: Co-mediatormentioning
confidence: 96%
“…The optically transparent GNP electrode turned out to be highly active for [Co(bpy-pz) 2 ] 3+/2 mediator [36] and even more for [Co(bpy) 3 ] 3+/2+ [35]. Al-Mamun et al [128] demonstrated a possibility of fabrication of FTO-free electrode based on graphene nanoplatelets. They combined GNP with silver nanowires, which themselves have poor electrocatalytic activity for [Co(bpy) 3 ] 3+/2+ .…”
Section: Co-mediatormentioning
confidence: 96%
“…Silver nanowire (Ag NW) mesh electrodes are often used in various electrochemical devices and DSSCs. [293][294][295][296][297][298][299][300][301][302][303] Al-Mamun et al 293 compared four types of CEs (Pt, AgNW, GNP (graphene nanoplatelets) and AgNW-GNP) for Co 3+ /Co 2+ redox mediator based DSSCs. Both AgNW and GNP showed inferior catalytic activity for the Co 3+ /Co 2+ redox couple.…”
Section: Other Metal Counter Electrodesmentioning
confidence: 99%
“…In this context, one report was found based on graphene/Ag NW composite electrodes with a PCE of 1.61%. 109 Nonmetallic NPs such as CoS, NiO, Ni 12 P 5 , and TiN have been used to fabricate graphene-based composite electrodes. 101,[110][111][112] CVD graphene/CoS composite electrodes showed a PCE of 3.42% with V OC , J SC , and FF of ;0.72 V, ;13.0 mA/cm 2 , and 36.40%, respectively.…”
Section: Graphene As Cathode Materialsmentioning
confidence: 99%